Effective Test Suite Optimization for Improving the Coverage Standards Using Hybrid Wrapper Filter Memetic Algorithm - Karuppusamy, P. (Journal of Soft Computing Paradigm, 2020)
The continuous progress and developments in the technologies related to the database and computer has heightened the significance of selecting the features. The most common methods that are used in choosing the features often come with the peril of choosing the features subsets that are unsuitable with the opted algorithm for the induction. Few methods that include the induction procedure for validating the subsets in the feature, despites its prediction capability is computationally more intensive. So to sort out the solution for the aforementioned problems, the proposed method in the paper utilizes the hybrid method for choosing the features clubbing the wrapper filter along with the structure of the Memetic to have an improved coverage-centered test-case escalation. The hybridized procedure optimizes the test suite integrating the call-stack along with it. The experimental observations obtained also exhibits the performance enhancement and the effective ness of the hybridized procedure that leads to cost factor minimization.